The relationship between board gender diversity and firm financial performance in the UK banking sector - Zhao, Ling-Zhu (2019)
Within the subject of corporate governance, gender diversity on board has turned into an important topic where a mass of studies aspires to investigate the influence of board gender diversity on firm financial performance. This paper examines the effect of female board participation on firm financial performance of the UK listed banks. By using a sample of 10 listed banks in FTSE350 during the research period 2008-2018 in a panel data analysis, this study finds that there are limited opportunities for appointment on women on the boards of the UK banking sector companies. Meanwhile, the main finding is that there is no significant relationship between female board representation and bank financial performance measured by both Tobin’s Q and ROA. The UK has been employing a voluntary gender quota regulation unlike many other EU countries, and there has always been a hot discussion on whether to implement the mandatory legislation. Thus, this research provides policy implications upon the gender quotas and encourages further studies to look into the potential explanations for the non-correlated link between gender diversity on board and firm financial performance.